Developing the skill of endotracheal intubation: implication for emergency medicine - Bernhard, Michael; Mohr, Stefan; Weigand, Markus A.; Martin, Evgenia; Walther, Andreas (Acta anaesthesiologica Scandinavica, 2012)
Background Securing the airway by means of endotracheal intubation (ETI) represents a fundamental skill for anaesthesiologists in emergency situations. This study aimed to evaluate the time needed by first-year anaesthesiology residents to perform 200 ETIs and assessed the associated success rates and number of attempts until successful ETI. Methods This prospective single centre study evaluated the number of working days, the success rate, the attempts needed until successful ETI in consecutive blocks of 25 ETI procedures and the related difficulties and complications. Results From 2007 to 2010, 21 residents were evaluated consecutively. These residents needed a mean (mean ± standard deviation) of 15.6 ± 3.0 days for 25 ETIs. Out of all residents 52% reached the target value of 200 ETIs after 50.2 ± 14.8 weeks of total working time. The ETI success rate after the first 25 ETIs increased steadily to the results after 200 ETIs (ETI success rate within one ETI attempt: 67% vs. 83%, P = 0.0001; ETI success rate within all ETI attempts: 82% vs. 92%, P = 0.0001). The number of attempts required until successful ETI decreased from 1.6 ± 0.8 after the first 25 ETIs to 1.3 ± 0.6 after 200 ETIs (P = 0.0001). Conclusion The increasing rate of relative ETI success and the decreasing rate of necessary attempts for successful airway management suggest a steadily increasing gain in ETI experience. The complications that developed during the first 200 ETI procedures justify supervision by a specialist in the field or a senior physician. Moreover, these results may influence the minimum requirement for qualification in anaesthesiology and emergency medicine.